Antimicrobial resistance: Moving from national action plans to national action - Moodley, Arshnee (2020)
Following the World Health Assembly’s endorsement of a global action plan to tackle antimicrobial resistance in 2015, the WHA urged all member states to put in place national action plans on Antimicrobial Resistance (AMR). Many low- and middle-income countries (LMICs) are poorly equipped to address problems related to AMR, and national action plans are important for defining and aligning investments. For those LMICs that have AMR national action plans in place, are these plans promoting action, or are they impediments to progress? Beyond national action plans, what needs to happen to prompt action against this multi-sectoral, life-threatening challenge? How can we retain and increase attention to AMR amid competing public health priorities, particularly Covid-19?